Preparation of TiO2 Nanotube Using Anodization Method: Charactherization and Its Application for CO Sensor - Harry Budiman; Rahmat Wibowo; Oman Zuas; Jarnuzi Gunlazuardi (EduChemia (Jurnal Kimia dan Pendidikan), 2021)
Preparation of highly ordered TiO2 nanotube arrays (HOTNAs) by anodization of Ti foil industrial grade in ethylene glycol electrolyte containing 0.3% of ammonium fluoride and 2% of water at 30 V for 90 minutes was conducted. The morphology structure, chemical composition, functional group, crystal phase, and optical properties of HOTNAs were characterized by field emission scanning electron microscope (FE-SEM), Energy Dispersive X-Ray (EDX),Fourier transform infra-red spectroscopy (FTIR), X-ray diffraction (XRD), and ultraviolet visible diffuse reflectance spectroscopy (UV/Vis-DRS). The well-ordered nanotube with vertically oriented structure was formed in the HOTNAs having  size in diameter, length, and wall thickness of  48,0 nm, 1,8 µm, and 26,7 nm, respectively. The fabricated HOTNAs were evaluated for their sensing properties for CO detection.  The results show that the fabricated HOTNAs were able to detect 2500 ppm of CO gas with response about 93,429 at operation temperature 150 °C. This preliminary study of sensing performance demonstrates that the prepared HOTNAs under this study is potential and promising as a material sensor for CO detection.